2019
DOI: 10.13057/biodiv/d200610
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Growth rate of Acropora muricata coral fragments transplanted on dome-shaped concrete artificial reef with different composition

Abstract: Abstract. Artificial reefs are artificial habitats laid in waters by mimicking some of the characteristics of natural reefs; and could be made of different materials, one of which is concrete. Seashell waste and stone ash could be added as an alternative material to the concrete for artificial reefs. The purpose of this research is to access the growth rate of Acropora muricata coral fragments transplanted on the hollow dome-shaped concrete with three different compositions: C1), conventional concrete, compose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 8 publications
(13 reference statements)
0
12
0
Order By: Relevance
“…Some previous studies of coral transplantation revealed that the growth rate of Acropora was higher than that of other hermatypic corals. Bongiorni et al (2011) reported that Acropora possesses relative growth ranged 66.9 to 83.3%, while growth rate of Acropora which transplanted on the artificial reef dome-shaped was 1.07 cm/month (Muzaki et al 2019), Acropora fragments fixed to the dead coral was 7.8 cm/year (Nithyanandan et al 2018). This result showed that the growth rate of both Acropora which transplanted on multilevel substrate possesses a high growth rate.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies of coral transplantation revealed that the growth rate of Acropora was higher than that of other hermatypic corals. Bongiorni et al (2011) reported that Acropora possesses relative growth ranged 66.9 to 83.3%, while growth rate of Acropora which transplanted on the artificial reef dome-shaped was 1.07 cm/month (Muzaki et al 2019), Acropora fragments fixed to the dead coral was 7.8 cm/year (Nithyanandan et al 2018). This result showed that the growth rate of both Acropora which transplanted on multilevel substrate possesses a high growth rate.…”
Section: Discussionmentioning
confidence: 99%
“…The HSAR can also generate beneficial vortices and turbulence, which is an attractive characteristic for habitat structures since fish abundance is influenced by current vortices [15]. Application of modified HSAR as platform for coral transplantation also reported by [4,6]. Dimension of the AR was 50x50 cm (diameter x height) and composed by a mixture of Portland cement, sand as fine aggregate and gravel as coarse aggregate (composition was 1:3:2).…”
Section: Artificial Reef Designmentioning
confidence: 99%
“…Previous study by [4] mentioned that live coral cover in the area is less than 15% in 2017 and mostly dominated by massive and encrusting lifeforms. Based on these conditions, it is clearly necessary to improve the condition of coral reefs in the area, by means of application of artificial reef [5] and/or coral transplantation [4,6]. In this study, we focused on the artificial reef which usually used to improve habitat quality as well as enhance marine resources, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As the results, increased shellfish production will have impact on increasing of the shell waste which reaches 90% from the total wet weight of the shellfish [2] and therefore will require serious handling. Generally, shell wastes will be thrown away or maybe 2 used as land filling material [2], or made into handicrafts, abrasive components in toothpaste, animal feed mixtures, absorbents for water management and other minor utilization [3]. In addition, shell waste also contains calcium carbonate, make it potentially utilized as a secondary base material for applications in a circular economy perspective, for example as a substitute material in cement mixtures [2,4].…”
Section: Introductionmentioning
confidence: 99%